Emotional reactivity: Beware its involvement in traffic accidents. (April 2018) - M'bailara, Katia; Atzeni, Thierry; Contrand, Benjamin; Derguy, Cyrielle; Bouvard, Manuel-Pierre; Lagarde, Emmanuel; Galéra, Cédric
Abstract: Background: Reducing risk attributable to traffic accidents is a public health challenge. Research into risk factors in the area is now moving towards identification of the psychological factors involved, particularly emotional states. The aim of this study was to evaluate the link between emotional reactivity and responsibility in road traffic accidents. We hypothesized that the more one's emotional reactivity is disturbed, the greater the likelihood of being responsible for a traffic accident. Methods: This case-control study was based on a sample of 955 drivers injured in a motor vehicle crash. Responsibility levels were determined with a standardized method adapted from the quantitative Robertson and Drummer crash responsibility instrument. Emotional reactivity was assessed with the MATHYS. Results: Hierarchical cluster analysis discriminated four distinctive driver's emotional reactivity profiles: basic emotional reactivity (54%), mild emotional hyper-reactivity (29%), emotional hyper-reactivity (11%) and emotional hypo-reactivity (6%). Drivers who demonstrated emotional hypo-reactivity had a 2.3-fold greater risk of being responsible for a traffic accident than those with basic emotional reactivity. Conclusion: Drivers' responsibility in traffic accidents depends on their emotional status. The latter can change the ability of drivers, modifying their behavior and thus increasing their propensity to exhibit risk behavior and to cause traffic accidents. Highlights: Emotional states are associated with responsibility in road traffic accidents. Emotional hypo-reactivity increases risk of being responsible for a traffic accident. Effect of emotional hypo-reactivity remains when controlling for external factors.